About a materialism of the trace in China - Jorge, Julia (Universidad Nacional del Litoral, 2020)
The syntagma trace materialism calls the meeting of dissimilar aesthetic, theoretical and philosophical projects that deal with materialism, writing, the materiality of writing. Taking into account these reflections, we will stop to observe one of the most singular writings for western thought: Chinese writing. Having as an end the deployment of articulations that define a materialist perspective centered on the matter as variation, modulation, deviation; from operations such as counterfeiting. To demonstrate these relationships, we will think about installations of the contemporary Chinese artist: Xu Bing.